Curcuminoid analogs inhibit nitric oxide production from LPS-activated microglial cells - Tocharus J. (2014)
The chemically modified analogs, the demethylated analogs 4-6, the tetrahydro analogs 7-9 and the hexahydro analogs 10-12, of curcumin (1), demethoxycurcumin (2) and bisdemethoxycurcumin (3) were evaluated for their inhibitory activity on lipopolysaccharide activated nitric oxide (NO) production in HAPI microglial cells. Di-O-demethylcurcumin (5) and O-demethyldemethoxycurcumin (6) are the two most potent compounds that inhibited NO production. The analogs 5 and 6 were twofold and almost twofold more active than the parent curcuminoids 1 and 2, respectively. Moreover, the mRNA expression level of inducible NO synthase was inhibited by these two compounds. The strong neuroprotective activity of analogs 5 and 6 provide potential alternative compounds to be developed as therapeutics for neurological disorders associated with activated microglia. © 2011 The Japanese Society of Pharmacognosy and Springer.